Cytokine Signatures Associated With Early Onset, Active Lesions and Late Cicatricial Events of Retinochoroidal Commitment in Infants With Congenital Toxoplasmosis. (5th March 2016) - Carneiro, Ana Carolina Aguiar Vasconcelos; Machado, Anderson Silva; Béla, Samantha Ribeiro; Costa, Julia Gatti Ladeia; Andrade, Gláucia Manzan Queiroz; Vasconcelos-Santos, Daniel Vitor; Januário, José Nélio; Coelho-dos-Reis, Jordana Grazziela; Ferro, Eloisa Amália Vieira; Teixeira-Carvalho, Andréa; Vitor, Ricardo Wagner Almeida; Martins-Filho, Olindo Assis
Abstract: Background. Ocular toxoplasmosis is a prominent and severe condition of high incidence in Brazil. The current study provides new insights into the immunological events that can be associated with retinochoroiditis in the setting of congenital toxoplasmosis in human infants. Methods. Flow cytometry of intracytoplasmic cytokines in leukocyte subsets following in vitro short-term antigenic recall in infants with congenital T. gondii infection. Results. Our data demonstrates that whereas neutrophils and monocytes from T. gondii –infected infants display a combination of proinflammatory and regulatory cytokine profiles, natural killer cells showed a predominantly proinflammatory profile upon in vitro T. gondii stimulation. The proinflammatory response of CD4 + and CD8 + T cells, characterized by the production of interferon γ (IFN-γ) and interleukin 17 in patients with an active retinochoroidal lesion, revealed the presence of IFN-γ and tumor necrosis factor α during early and late immunological events. This specific proinflammatory pattern is associated with early events and active retinochoroidal lesion, whereas a robust monocyte-derived interleukin 10–mediated profile is observed in children with cicatricial ocular lesions. Conclusions. These findings support the existence of a progressive immunological environment concomitant with the initial, apical, and cicatricial phases in the process of retinochoroidal lesion formation in infants with congenital toxoplasmosis that may be relevant in the establishment of stage-specific clinical management.